Družbeni proizvod slovenskih mest - Vrišer, Igor (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 1997)
On the basis of data on the GDP produced in Slovenian towns in 1990, gathered by the Statistical Office of the Republic of Slovenia, the following topics are presented: (1) the importance and percentage of Slovenian GDP produced in towns; (2) the percentage of GDP per an urban or rural inhabitant; (3) the activities which have contributed the most to the produced GDB; (4) a functional definition of towns was made according to the activity structure (primary, secondary, tertiary, quaternary) of the GDP produced in towns; (5) acomparison with a similar analysis of 1966 showed changes in the significance of towns, which was due to the influence of the post-War socio-economic development.
Keywords: družbena geografija; družbene dejavnosti; družbeni produkt; ekonomska geografija; geografija naselij; gospodarske dejavnosti; human geography; mesta; Slovenia; Slovenija